Branding Desa Mandiri Sampah: Wujudkan Tata Kelola Sampah yang Berkelanjutan di Gampong Drien Rampak, Johan Pahlawan Kabupaten Aceh Barat - Ikhsan Ikhsan; Akmal Saputra; Vellayati Hajad; Ikhwan Rahmatika Latif; Fadli Afriandi; Yeni Sri Lestari (Universitas Teuku Umar, 2024)
This community service program in Drien Rampak Village, Johan Pahlawan Aceh Barat, aimed to establish a sustainable waste management system through the